N-glycosylation-mutated HCV envelope glycoprotein complex enhances antigen-presenting activity and cellular and neutralizing antibody responses - Ren, Yushan; Min, Yuan-Qin; Liu, Min; Chi, Lianli; Zhao, Ping; Zhang, Xiao-Lian (Biochimica et biophysica acta, 2016)
The development of an efficient vaccine and broadly cross-neutralizing antibodies of hepatitis C virus (HCV) remains a priority. The heavily glycosylated viral envelope glycoprotein E1E2 complex is a candidate vaccine antigen. Bacteria-derived unmethylated CpG DNA, a potent stimulator of immune cells, is important for vaccine research. Here, the immunogenicities of wild type (WT) E1E2, five N-glycosylation site mutated E1E2 glycoproteins, and five CpG-coupled E1E2 N-glycosylation mutated glycoproteins were analyzed in BALB/c mice by DNA vaccination using in vivo electroporation. The E1E2 protein expression levels were examined and shown to be unaffected by these N-glycosylation mutations. We found that a CpG-coupled E1-N209D-E2-N430D DNA vaccine (named CpG-E1E2-M4) induced the highest cellular immune response compared to the WT E1E2, CpG-E1E2, and other mutants. Furthermore, the CpG-E1E2-M4 anti-serum effectively neutralized the infection of cell-cultured HCV (HCVcc, genotype 2a)- and HCV pseudo particles (HCVpp, genotypes 1 to 7) to Huh-7.5.1 hepatocytes. Additionally, CpG-E1E2-M4 enhanced the Interleukin-12 (IL-12) production and antigen-presenting activity of CD11c+ dendritic cells (DCs) by inducing CD4+ Th1 polarization and the production of perforin and granzyme B (GrB) in CD8+ T cells. As our knowledge this is the first study revealing that the naturally poor immunogenicity of E1E2 can be enhanced by the deletion of N-glycans combined with the addition of immune activator CpG by DNA vaccination. Deletion of N-glycans can enhance viral immunogenicity. The selected CpG-E1E2-M4 mutant is a novel potential HCV DNA vaccine that elicits enhanced CD4+ Th1 and CD8+ T cell responses and neutralizing antibody production against HCV infection. This article is part of a Special Issue entitled "Glycans in personalised medicine" Guest Editor: Professor Gordan Lauc. •The immunogenicities of HCV E1E2 and its N-glycan deletion mutants were analyzed.•A mutant (named CpG-E1E2-M4) induces the strongest Th1 and CTL responses.•CpG-E1E2-M4 induces the highest neutralizing protective antibody activity.•The poor immunogenicity of E1E2 can be enhanced by the deletion of N-linked glycans.•The CpG-E1E2-M4 E1E2 DNA vaccination may benefit the prevention and treatment of HCV.